Filamin A interacts with the coactivator MKL1 to promote the activity of the transcription factor SRF and cell migration - Kircher, Philipp; Hermanns, Constanze; Nossek, Maximilian; Drexler, Maria Katharina; Grosse, Robert; Fischer, Maximilian; Sarikas, Antonio; Penkava, Josef; Lewis, Thera; Prywes, Ron; Gudermann, Thomas; Muehlich, Susanne (Science Signaling, 2015)
Megakaryoblastic leukemia 1 (MKL1) is a coactivator of serum response factor (SRF) that promotes the expression of genes associated with cell proliferation, motility, adhesion, and differentiation-processes that also involve dynamic cytoskeletal changes in the cell. MKL1 is inactive when bound to monomeric globular actin (G-actin), but signals that activate the small guanosine triphosphatase RhoA cause actin polymerization and MKL1 dissociation from G-actin. We found a new mechanism of MKL1 activation that is mediated through its binding to filamin A (FLNA), a protein that binds filamentous actin (F-actin). The interaction of FLNA and MKL1 was required for the expression of MKL1 target genes in primary fibroblasts, melanoma, mammary and hepatocellular carcinoma cells. We identified the regions of interaction between MKL1 and FLNA, and cells expressing an MKL1mutant that was unable to bind FLNA exhibited impaired cell migration and reduced expression of MKL1-SRF target genes. Induction and repression of MKL1-SRF target genes correlated with increased or decreased MKL1-FLNA interaction, respectively. Lysophosphatidic acid- induced RhoA activation in primary human fibroblasts promoted the association of endogenous MKL1 with FLNA, whereas exposure to an actin polymerization inhibitor dissociated MKL1 from FLNA and decreased MKL1-SRF target gene expression in melanoma cells. Thus, FLNA functions as a positive cellular transducer linking actin polymerization toMKL1-SRF activity, counteracting the known repressive complex of MKL1 and monomeric G-actin.
CRIS-Team Scopus Importer:2024-07-10